Subtotal cholecystectomy: An operative option for Salmonellae typhi gangrenous cholecystitis. Issue 11 (15th July 2020) - Akello, Vivian Valin; Bitamazire, Denis; Wandabwa, Joel; Ssebuufu, Robinson
Abstract: Typhoid gangrenous cholecystitis is uncommon and can be managed by subtotal cholecystectomy with nonclosure of the cystic duct if that is required for patient safety. Abstract : Typhoid gangrenous cholecystitis is uncommon and can be managed by subtotal cholecystectomy with nonclosure of the cystic duct if that is required for patient safety.